2021
DOI: 10.1186/s12986-021-00587-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptation is associated with less weight and fat mass loss in response to low-energy diets

Abstract: Background The practical relevance of metabolic adaptation remains a controversial issue. To the best of our knowledge, no study has properly evaluated the role of metabolic adaptation in modulating weight loss outcomes. Therefore, the aim of this study was to determine the association between metabolic adaptation, at the level of resting metabolic rate (RMR), and weight and fat mass (FM) loss after low-energy diets (LED), after adjusting for dietary adherence and other confounders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…The present findings are in line with recent data from our group showing that metabolic adaptation at the level of RMR was associated with less weight and FM loss following low‐energy diets in individuals with obesity (21). Moreover, Goele and colleagues (31) reported that in women who experienced metabolic adaptation after a low‐energy diet, 38% of the difference between measured and predicted weight loss was due to metabolic adaptation at the level of RMR.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present findings are in line with recent data from our group showing that metabolic adaptation at the level of RMR was associated with less weight and FM loss following low‐energy diets in individuals with obesity (21). Moreover, Goele and colleagues (31) reported that in women who experienced metabolic adaptation after a low‐energy diet, 38% of the difference between measured and predicted weight loss was due to metabolic adaptation at the level of RMR.…”
Section: Discussionsupporting
confidence: 93%
“…We have confirmed these findings in two recent studies (19,20) by showing that metabolic adaptation at the level of RMR, after weight loss, was not associated with weight regain up to 2 years of follow‐up. Moreover, in another recently published manuscript, our research group showed that metabolic adaptation at the level of RMR was associated with less weight and fat mass (FM) loss in response to a low‐energy diet, in men and women with obesity (21). However, it remains to be investigated whether metabolic adaptation contributes to resistance to weight loss by increasing the time necessary to achieve weight loss goals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compensatory responses in REE during negative energy balance that are independent of changes in FM and FFM (i.e., AT) may attenuate weight loss ( 4 , 28 , 29 ). Therefore, identifying predictors of metabolic adaptation may contribute to better treatment of obesity and weight management ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…An observed response to caloric restriction and weight loss is adaptive thermogenesis (AT), which is a reduction in energy expenditure related to improved cellular energy efficiency that is independent of changes in fat mass (FM) and fat-free mass (FFM). AT persists in the weight-reduced state ( 3 ) and during the dynamic process of negative energy balance, and may limit the ability to effectively maintain weight loss ( 4 ).…”
Section: Introductionmentioning
confidence: 99%